A survey on the practice and status of psychotherapy in the Philippines. [article]. - Teh, Lote A.
To find out what the practice of psychology is like in the country, forty-eight practicing psychotherapists were interviewed using a24-item interview schedule. The main findings of the survey are the following:(a)the most common problems encountered by the respondents were school-related problems of the children and adolescents, marital, and family problems; (b)almost all the respondents use the eclectic approach; (c)most of them use a sliding scale in charging their clients; (d)although there was agreement that psychotheraphy is a good career option, the respondents also pointed out the areas that need improvement; and (e)they were almost unanimous in expressing the need to professionalize the practice of psychotheraphy. The implications of these results in terms of the training and regulation of psychotheraspist were discussed.